Controlled Scallop Height Tool Path Generation for 3-Axis Vertical CNC Machining of STL Surfaces - Rajiv (My University, 2014)
Sculpture surface machining is widely used in these days to make intricate products. NC machining of sculpture surfaces require effective tool path positioning and planning. Formation of scallops between two neighboring tool paths is the main problem that occurs while NC machining which directly results increase in machining time. Although several methods are using for sculpture surface machining for tool path generation with ball nose ended milling cutters but Iso-parametric, Iso-planar and Iso-scallop methods are commonly used. Among all these methods iso-scallop method is widely used because it requires less machining time and produces uniform surface roughness. It is also important to identify the minimum NC tool path length for iso-scallop machining. For small path segments of tool paths, the machining time would rapidly increase, especially for high speed machining. Ideal segment length and side step are thus necessary for proper iso scallop machining. In this present work, scallop height measure in real and global sense is obtained by application of iso-scallop strategy. For controlled scallop height, proper orientation of cutter path and planning is required. For tool path positioning and planning, “ball drop” and iso-scallop methods respectively are used here to develop a new methodology. It is concluded that scallops are difficult to remove but in this present work, by calculating the maximum scallop height with ball ended milling cutters to achieve controlled scallop height tool path on triangulated surfaces is done. Mathematical calculations of tool path positioning and planning are also done with real sense. To achieve controlled scallop height tool path, bisection method is used.
ME-CAD/CAM-Dissertation
Keywords: Controlled Scallop Height Toolpath; NC toolpath planning for Ball End Mill Cutter; STL Surfaces; 3-axis vertical CNC machining; mechanical engineering; MED